Trilha interpretativa : um processo de reflexão-na-ação do docente de ciências da natureza - Castro, Edward Bertholine de (2012)
The relevance and the role of teachers and its formal duty is unquestionable to young people engaged in criticism and consciously their citizenship, as well as to the promotion of a scientific, technical training and cultural significance,. This study aimed to provide the rethinking of teaching practice to build pedagogical strategies that help elementary educators to encourage students to socio-environmental issues by guiding their vision of the environment where they live and interact on a daily basis. Another goal was to provide the teachers empowerment, guiding principles, and potentialities of classroom activity, whereas collective field strategy work and therefore, dialogic might facilitate the deployment of education by the knowledge area and curriculum guidelines. To achieve it, we used qualitative research, and the action-research was the responsible of the process of understanding the investigated problem for possible improvement through the application of a questionnaire semistructured with nine questions involving (1) knowledge on teaching differences by area of knowledge and by discipline (2) interdisciplinary activities and (3) the connection of administrative management with pedagogical activities. In general, we realized that most of participating teachers in this study demonstrated ignorance of ideological relations regarding scientific production and, consequently, with the formulation of curriculum and educational programs, training, were in fact interpreted as a closer view of common sense in understanding the basic principles of curriculum guidelines in Mato Grosso state.